2022
DOI: 10.1038/s41598-022-08103-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenome of a stink worm (Annelida: Travisiidae) includes degenerate group II intron that is also found in five congeneric species

Abstract: Mitogenomes are useful for inferring phylogenetic relationships between organisms. Although the mitogenomes of Annelida, one of the most morphologically and ecologically diverse metazoan groups have been well sequenced, those of several families remain unexamined. This study determined the first mitogenome from the family Travisiidae (Travisia sanrikuensis), analyzed its mitogenomic features, and reconstructed a phylogeny of Sedentaria. The monophyly of the Terebellida + Arenicolida + Travisiidae clade is supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…This is the first study to determine the mitogenome sequence of Arenicolidae using Abarenicola claparedi oceanica and perform phylogenetic analyses using closely related families registered in GenBank. Using previously published mitogenome data (Bolbat et al, 2021;Nam et al, 2021;Kobayashi et al, 2022aKobayashi et al, , 2022b, mitogenomic phylogenetic trees were reconstructed with the most inclusive taxon sampling of the part of the Sedentaria families (oligochaetes, hirudineans, echiurans and some polychaetes). Analyses based on the nucleotide sequences confirmed the monophyly of Terebellidae, which was paraphyletic in analyses based on the amino acid sequences and previous mitogenomic phylogenies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the first study to determine the mitogenome sequence of Arenicolidae using Abarenicola claparedi oceanica and perform phylogenetic analyses using closely related families registered in GenBank. Using previously published mitogenome data (Bolbat et al, 2021;Nam et al, 2021;Kobayashi et al, 2022aKobayashi et al, , 2022b, mitogenomic phylogenetic trees were reconstructed with the most inclusive taxon sampling of the part of the Sedentaria families (oligochaetes, hirudineans, echiurans and some polychaetes). Analyses based on the nucleotide sequences confirmed the monophyly of Terebellidae, which was paraphyletic in analyses based on the amino acid sequences and previous mitogenomic phylogenies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the mitogenomic phylogeny indicated a close relationship between Travisiidae and the Terebellida and Arenicolida clade (Kobayashi et al ., 2022 a ). However, the phylogenetic position was not sufficiently clarified as the position of Travisiidae was poorly supported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such taxonomic distribution is often used as empirical support for mutational-pressure hypothesis explaining lack of introns in fast-evolving mtDNA [34]. Up to this point, the only bilaterian animals where mitochondrial intronic sequences have been identified are several species of annelids [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%